Improvement of strength and water absorption of Interlocking Compressed Earth Bricks (ICEB) with addition of Ureolytic Bacteria (UB) - Zamer, M.M.; J.M., Irwan; Othman, N.; Khalid, F.S. (Construction Research Institute of Malaysia (CREAM), 2018)
Interlocking Compressed Earth Brick (ICEB) are cement stabilized soil bricks that allow for dry stacked construction. This characteristic resulted to faster the process of building walls and requires less skilled labour as the bricks are laid dry and lock into place. However there is plenty room for improving the interlocking bricks by increase its durability. Many studies have been conducted in order to improve the durability of bricks by using environmentally method. One of the methods is by introducing bacteria into bricks. Bacteria in brick induced calcite precipitation (calcite crystals) to cover the voids continuously. Ureolytic Bacteria (UB) was used in this study as a partial replacement of limestone water with percentage of 1%, 3% and 5%. Enrichment process was done in soil condition to ensure the survivability of UB in ICEB environment. This paper evaluates the effect of UB in improving the strength and water absorption properties of ICEB and microstructure analysis. The results show that addition of 5% UB in ICEB indicated positive results in improving the ICEB properties by 15.25% in strength, 14.72% in initial water absorption and 14.68% reduction in water absorption. Precipitation of calcium carbonate (CaCo3) in form of calcite can be distinguish clearly in microstructure analysis.